(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Barulina Y. О. Methodological preconditions of understanding of value-semantic consciousness essence in space of student-centered lesson. The article discusses various theoretical approaches to the concept of «student-centered learning», «student-centered lesson», philosophical, psychological and educational preconditions value-semantic consciousness development of seniors in space of student-centered lesson.